2009
DOI: 10.1002/vnl.20170
|View full text |Cite
|
Sign up to set email alerts
|

Color inhibition of phenolic antioxidants in Ziegler‐Natta polyethylene. I. In‐situ polymer studies

Abstract: Although the level of transition-metal catalyst residues in polyethylene (PE) has been drastically reduced over the years, they can still give rise to discoloration, particularly when associated with other additives such as antioxidants. This first of this series of papers screens a variety of candidate color suppressants featuring a range of functional groups, including alcohols, amine/ sulfur compounds, and acid-containing species. These candidate color suppressants were melt-blended into a Ziegler-Natta lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Phosphites are known to reduce color development in polyolefins whereas hindered phenols cause discoloration. Such effects have been mainly attributed to formation of colored transformation products, including quinoid/stilbene and carbonyl species, and also to colored complexes formed via chelation of metallic catalyst residues with phenolic AOs and associated transformation products [18]. The formulation showing the most severe yellowing was that containing V‐4010 which itself is actually brown in color to start with, though the good melt stabilization activity also suggests formation of colored transformation products.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphites are known to reduce color development in polyolefins whereas hindered phenols cause discoloration. Such effects have been mainly attributed to formation of colored transformation products, including quinoid/stilbene and carbonyl species, and also to colored complexes formed via chelation of metallic catalyst residues with phenolic AOs and associated transformation products [18]. The formulation showing the most severe yellowing was that containing V‐4010 which itself is actually brown in color to start with, though the good melt stabilization activity also suggests formation of colored transformation products.…”
Section: Resultsmentioning
confidence: 99%
“…[ 50,51 ] In situ studies in Zeigler‐Natta polyethylene confirm the findings that both the use of dipentaerythritol (DPE) and triisopropylamine (TIPA) gave excellent color inhibition when used with highly color forming phenolic antioxidants. [ 51,52 ] When the study was extended to the solution phase, [ 53 ] it was confirmed that the actual color was due to the formation of titanium‐based phenolates and that the DPE and TIPA operated through competitive complexation with the phenol for the titanium ions.…”
Section: Thermal and Photochemical Stabilizersmentioning
confidence: 99%
“…However, it is possible that oxidation is concentrated in the black spots that were formed in the material (see Figure 8) and that could not be examined by color, UV-Vis, and FTIR measurements. The black spots are probably formed when catalyst residues from polymer synthesis, like titanium chloride (e.g., TiCl 3 ) and chromium (Cr) particles, react with the phenolic antioxidant to produce chromophoric species, such as titanium phenolates [34][35][36][37]. As these catalyst residues promote hydroperoxide decomposition [38], oxidation preferentially starts at the polymercatalyst interface.…”
Section: Ftir Spectroscopy Ftir Spectroscopy Results Are Shown Inmentioning
confidence: 99%